Influence of energy recovery system on the energy efficiency of a flat-bed dryer in the drying of turmeric - Adu, E. A.; Pandiarajan, T.; Farzana, W.; Abba, K. A. K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Drying is one of the most energy intensive unit operations in agricultural and food processing industry. Energy costs represent a major fraction of cost of operation of a mechanical dryer, therefore, the more efficient a dryer uses its energy supply, the lesser its cost of operation and the better it impacts on profitability of drying process. A flat-bed dryer of 25kg capacity was developed and fitted with air-to-air indirect mixing heat exchanger (Heat Recovery Unit, HRU) at the vent of the drying chamber. The dryer was tested to determine the impact of exhaust vent waste heat recovery on its energy efficiency and cost of operation. Turmeric, an important spice crop was dried at three temperatures of 60°C, 65°C, and 70°C under two operating conditions; (i) without HRU (C-I) and (ii) with HRU (C-II). The result show thermal efficiency, at C-I it was found to be 28%, 27% and 27% at 60°C, 65°C and 70°C respectively and for C-II it was 42%, 42%, and 40% at 60°C, 65°C, and 70°C respectively. This indicates that the overall thermal efficiency was improved by 15% for C-II at 65°C as compared to C-I at 65°C. ANOVA show there is significant different (P< 0.05) between C-II and C-I as regards thermal efficiency. The result also showed that specific energy consumption was reduced for all drying temperatures levels of C-II as compared to C-I and the result shows that testing condition C-II, at 65°C has the lowest specific energy consumption of 1.79(kWh/kg) while C-I at 60°C has the highest value; 2.37 (kWh/kg), this showed significant different (P< 0.05).Drying curves of turmeric were plotted and it was found that C-II performed better in drying turmeric since the moisture lose was faster than in C-I and the drying time was lowered by 4hrs for C-II at 65°C compared to C-I 65°C. The average Return on Investment (ROI) of HRU was calculated considering average of 260 working days or 130 batch drying operation per annum with one drying cycle per two working days and was found to be 0.61 and the payback period was 19 months. It was concluded that the developed flatbed dryer can be used to dry 25 kg of turmeric per batch in 25 hours drying time using operating condition C-II, 65°C which showed better quality in terms of energy efficiency and drying rate.